Relationship between oxytocin and serotonin and the fearfulness, dominance, and trainability of horses - Kim, Junyoung (J Anim Sci Technol, 2021)
Oxytocin (OXT) and serotonin (5-HT) are essential neurotransmitters associated with the behavior of animals. Recently, we found that the plasma concentration of OXT is positively correlated with horse docility and friendliness toward humans. However, the relationships between the neurotransmitters and other temperaments such as fearfulness, dominance, and trainability are unknown. This study aimed to identify whether the plasma concentration of OXT or 5-HT is correlated with fearfulness, dominance, and trainability of horses. Blood samples of 34 horses were collected at the Horse Industry Complex Center of Jeonju Kijeon College. The concentration of OXT and 5-HT was measured in the plasma samples using enzyme-linked immunosorbent assays. The fearfulness, dominance, and trainability of horses were scored by three professors who were very familiar with the horses. One-way analysis of variance with the least significant difference post-hoc analysis was used to compare the scores for fearfulness and dominance among groups. The trainability of horses was compared using the student t-test. The 5-HT was negatively correlated with dominance, but it had no relation with fearfulness. The OXT appeared to be negatively correlated with fearfulness and dominance in horses. Furthermore, OXT was positively correlated with the trainability of horses. Additionally, 5-HT appeared to enhance trainability. In conclusion, the concentration of OXT or 5-HT in horse blood plasma can be used as a biomarker to monitor the fearfulness, dominance, or trainability of horses.